Predictors of Academic Success in First Semester Nursing Students - Dumitrescu, Cristina; Kupczynski, Lori; Campo, Marc (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
The anticipated nursing shortage requires a closer look at academic predictors of success for first-year nursing students. Literature shows that there is a significant shortage of students graduating from nursing programs to replace the nurses leaving the workforce. This study examined whether self-efficacy and self-esteem predict student success for first-year baccalaureate nursing students taking an introductory science course: Biology for Science Majors (BIO 130). Understanding the relationships between self-efficacy, self-esteem, and the end-of-course grade to measure academic success can inform future student success programming for undergraduate nursing students. The study used a correlation design to determine relationships between students’ self-efficacy, self-esteem, and academic success. The independent variables were self-efficacy and self-esteem. The dependent variable was student academic success measured by students’ final course grades. Pearson correlation and linear regression analysis indicated a weak relationship between scores on the General-Self-Efficacy Scale (GSES) and final course grades. Similarly, a weak relationship was found between scores on the Rosenberg Self-Esteem Scale (RSES) and the final course grades. This finding remained consistent when controlling for each independent variable.